2022
DOI: 10.3390/ijms23073666
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Mitochondria as Modulators of Blood Platelet Activation and Reactivity in Diabetes and Effect of Metformin on Blood Platelet Bioenergetics and Platelet Activation

Abstract: Blood platelet dysfunctions are strongly involved in the development of the micro- and macrovascular complications in diabetes mellitus (DM). However, the molecular causes of abnormal platelet activation in DM remain unclear. Experimental data suggests that platelet mitochondria can regulate the prothrombotic phenotype of platelets, and changes in these organelles may influence platelet activation and modify platelet responses to stimulation. The present study evaluates the impact of DM on mitochondrial respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…5). T2D mice show higher baseline platelet mitochondrial respiration (23), consistent with hyperglycemia-induced increase in glucose metabolism (24). There were no differences with Metformin treatment in any of the parameters we interrogated in T2D treated mice compared to controls (Fig.…”
Section: Resultssupporting
confidence: 53%
“…5). T2D mice show higher baseline platelet mitochondrial respiration (23), consistent with hyperglycemia-induced increase in glucose metabolism (24). There were no differences with Metformin treatment in any of the parameters we interrogated in T2D treated mice compared to controls (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Accumulating studies establish a role for mitochondrial dysfunction in platelets in T2D [23] . Therefore, we decided to measured platelet mitochondrial bioenergetics in our model.…”
Section: Resultsmentioning
confidence: 99%
“…Specific mechanisms leading to increased platelet reactivity have not fully been elucidated, but include increased platelet receptor density, increased Ca 2+ signaling and hyperreactivity to platelet agonists [79–81]. Recent work linked platelet mitochondrial impairment to the dysregulation in platelet function observed in diabetes [82 ▪▪ ,83]. Mitochondrial stress tests, which calculate mitochondrial efficiency in various metabolic processes, have shown that resting platelets from diabetic patients have lower maximal respiration compared with nondiabetic patients [25,82 ▪▪ ,83].…”
Section: Pathologic Mitochondrial Function In Plateletsmentioning
confidence: 99%
“…Recent work linked platelet mitochondrial impairment to the dysregulation in platelet function observed in diabetes [82 ▪▪ ,83]. Mitochondrial stress tests, which calculate mitochondrial efficiency in various metabolic processes, have shown that resting platelets from diabetic patients have lower maximal respiration compared with nondiabetic patients [25,82 ▪▪ ,83]. Activation of diabetic platelets with thrombin further accentuated differences in maximal respiration, while also demonstrating a decrease in basal oxygen rate consumption (OCR) and ATP production [82 ▪▪ ].…”
Section: Pathologic Mitochondrial Function In Plateletsmentioning
confidence: 99%